Structural-semantic particularities of the names-precedents in the Chinese discourse - N N Voropaev (Vestnik Rossijskogo universiteta družby narodov. Seriâ Lingvistika, 2011)
The author suggests according to the real working of the names-precedents in the discourse to differentiate the names-precedents-references and the names-precedents-descriptions.